A case–control study to assess the ability of the thymine challenge test to predict patients with severe to life threatening fluoropyrimidine‐induced gastrointestinal toxicity. Issue 1 (12th December 2019) - Helsby, Nuala A.; Duley, John; Burns, Kathryn E.; Bonnet, Claire; Jeong, Soo Hee; Brenman, Elliott; Barlow, Paula; Sharples, Katrina; Porter, David; Findlay, Michael
Abstract : Aims: A previous study suggested that a thymine (THY) challenge dose could detect aberrant pharmacokinetics in known cases of fluoropyrimidine toxicity compared with healthy volunteers. The preliminary data suggested that urine sampling also could detect this aberrant disposition. The aim of this case–control study was to assess the ability of the urinary THY challenge test to discriminate cases of severe gastrointestinal toxicity in a cohort of patients treated with 5‐fluorouracil or capecitabine. Methods: Patients ( n  = 37) received a 250 mg ( per os ) dose of THY and a cumulative urine sample was collected for 0–4 h. The urinary amounts of THY and metabolite dihydrothymine (DHT) were determined by liquid chromatography/mass spectrometry. Genomic DNA was analysed for DPYD gene variants. Renal function was estimated from blood creatinine levels. Cases ( n  = 9) and noncases ( n  = 23) of severe (grade ≥ 3) gastrointestinal toxicity were defined based on Common Terminology Criteria for Adverse Events. Results: The median THY/DHT ratios were 6.2 (interquartile range 2.9–6.4) in cases, including the 2 patients who were DPYD heterozygous carriers. However, this was not significantly different ( P  = .07) from the THY/DHT in noncases (median 2.6, interquartile range 2.8–4.2). Although creatinine clearance was lower ( P  = .001) in cases, renal function could not discriminate cases from noncases. However, logistic regression analysis using both of these explanatory variables could discriminate most cases (receiver operating characteristic area 0.8792, 95% confidence interval 0.72–1.00). Conclusions: The THY challenge test combined with a patient's renal function may be useful as a phenotypic diagnostic test to detect risk of life‐threatening fluoropyrimidine gastrointestinal toxicity.